Efficiency Analysis of the Indonesian Financial Institution Subsector: A Dea Approach - Soewignyo, Fanny (JBE (Journal of Business and Economics), 2010)
This paper applies Data Envelopment Analysis in measuring and analyzing the relative efficiency of 11 Indonesian financial companies listed in Indonesia stock Exchange (IDX). DEA measures the efficiency of decision making units (DMUs) by doing linear program for each one as a comparison to other units. Accordingly the DMUs that lie on frontier curve are efficient. Whereas the DMU that is not lie on the curve is considered inefficient. This paper shows that only three companies are fully efficient (100%) in both CCR and BCC scores. This indicates that those companies are operating in the most productive scale size. In addition to identifying best-practice companies and those that are out-of-line with the best practice companies, DEA also points to the specific changes that must be made in the less productive companies in order for them to catch up with their best-practice peer group. The findings of this study should help the managers in financial institution to put more efforts into efficiency improvement.